2009
DOI: 10.1176/appi.neuropsych.21.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Is Not Depression in Huntington's Disease

Abstract: Apathy and depression are common neuropsychiatric features of Huntington's disease. The authors studied a group of 34 Huntington's disease patients. In addition to the conventional classification according to DSM-IV criteria of depression, emphasis was put on a dimensional approach using scores on several different scales. Severe depression was found in 12% and severe apathy in 52% of all study patients. The authors found that apathy and depression are not related and are clearly distinct dimensions. Apathy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 0 publications
8
42
0
Order By: Relevance
“…Only a few questions were inconsistent with others in the eight factors, particularly questions regarding anxiety, which were present in 3 different factors. Although there is evidence that apathy is a distinct syndrome in HD that correlates with disease progression (Levy et al 1998; Naarding et al 2009; van Duijn et al 2010), we included UHDRS questions regarding apathy in the factor analysis and found that they loaded onto the same factor as depressed mood. Factor models of the BDI-II have been proposed, often dividing the scale into somatic or cognitive (negative thoughts about oneself) domains as primary factors, with affective symptoms loading onto one or the other (Ward 2006; Chilcot et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few questions were inconsistent with others in the eight factors, particularly questions regarding anxiety, which were present in 3 different factors. Although there is evidence that apathy is a distinct syndrome in HD that correlates with disease progression (Levy et al 1998; Naarding et al 2009; van Duijn et al 2010), we included UHDRS questions regarding apathy in the factor analysis and found that they loaded onto the same factor as depressed mood. Factor models of the BDI-II have been proposed, often dividing the scale into somatic or cognitive (negative thoughts about oneself) domains as primary factors, with affective symptoms loading onto one or the other (Ward 2006; Chilcot et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that distinct syndromes of depression and apathy exist in HD and should be examined and treated independently [22]. Apathy is common in HD, developing as early as in the prodromal period [23], and it is more prevalent than depression in HD [24,25]. Unlike depression, apathy has been shown to increase with disease progression and to correlate with motor symptoms and cognitive dysfunction [25].…”
Section: What Is the Relationship Of Biological And Social Factors Withmentioning
confidence: 99%
“…Unlike depression, apathy has been shown to increase with disease progression and to correlate with motor symptoms and cognitive dysfunction [25]. Antidepressants are often prescribed to treat apathy, but the effectiveness of this treatment or any other is entirely unknown [24]. …”
Section: What Is the Relationship Of Biological And Social Factors Withmentioning
confidence: 99%
“…Still, not all psychiatric symptoms in HD patients clearly progress with age either [50]. For example, while apathy appears to progressively worsen, depression does not [22,5052]. Performance in the progressive ratio test at satiety has been suggested to be primarily affected by the rats’ hedonic value of the food reward, while motivation to perform the test during food restriction is thought to be more governed by the induced energy imbalance (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Using this protocol, we found that BACHD rats were less motivated than their WT littermates to perform the test. This was an interesting phenotype on its own, as it might be related to apathy symptoms that are frequently found in HD patients [21,22]. However, as the BACHD rats are obese without showing an increased body weight it would also mean that they likely carried more adipose tissue compared to WT rats during this restriction protocol.…”
Section: Introductionmentioning
confidence: 99%